GENERAL FRAMEWORK FOR PUBLISHING OF MATHEMATICAL WEB APPLICATIONS (Journal of Information Technologies in Education (ITE), 2009)
This system would allow an easy way to bring mathematical applications to the Internet. Although the automated generation of PhP scripts is a simple task, there is no system that would allow bringing mathematical application written in any locally based system to the web. The main part of such system is simple XML-based language that fully describes source mathematical application.
Keywords: framework; mathematical programming; web publishing; XML